Synthesis of Antibacterial and Antifungal Activity of Metal (II) Complexes with Schiff Base Derived from 3-Methoxy-5-Bromosalicylaldehyde - Bakirdere, Emine Gulhan; Canpolat, Erdal; Kaya, Mehmet (Chem Soc Pakistan, 2013)
In this study, the complexes of Co (II), Ni (II), Cu (II) and Zn (II) with 2-{(E)-[(4-aminophenyl)imino]methyl}-4-bromo-6-methoxyphenol were prepared and characterized by physical, spectral and analytical data. The metal: ligand stoichiometric ratio is 1: 2 in all the complexes. It was determined that the bidentate behavior of the ligand is accomplished via the phenolic oxygen and the azomethine nitrogen atoms. Both the antibacterial and antifungal activities and MIC values of compounds were reported. Among the tested compounds, the most effective compound providing a MIC value of 64 mu g/mL are Zn(L)(2) against C. tropicalis and B. subtilis.
Keywords: Schiff base; transition metal complexes